Lipophilic poly(glycolide) blocks in morpholin-2-one-based CARTs for plasmid DNA delivery: Polymer regioregularity, sequence of lipophilic/polyamine blocks, and nanoparticle stability as factors of transfection efficiency. (5th December 2022) - Shaputkin, Evgeny D.; Nifant'ev, Ilya E.; Bagrov, Vladimir V.; Shlyakhtin, Andrey V.; Abashkin, Dmitrii A.; Galiakberova, Adelya A.; Ivchenko, Pavel V.
Graphical abstract: Highlights: Block copolymers of substituted glycolides and N -BOC-morpholin-2-one are obtained. After hydrolysis, amphiphilic polyester/polyamine copolymers form micelles. ζ-potential inversion at pH ∼ 7 correlates with optimum length of the polyamine block. Irregular microstructure of the poly(glycolide) block is required for transfection. N/P ratios, optimized for pDNA polyplexes by DLS and transfection studies, coincide. Abstract: In the present work, monosubstituted glycolides (G2 –G4 ) derived from the ( L )-tyrosine-based glycolide G1 and containing –CH2 C6 H4 OR substituents (R = decanoyl, oleoyl, C(O)CH( n -C6 H13 )( n -C8 H17 )) have been used to design biodegradable and biocompatible lipophilic blocks in N -BOC-morpholin-2-one (M1 )-based Charge-Altering Releasable Transporters (CARTs). Copolymers of dodecyl carbonate C1 (the 'benchmark' lipophilic comonomer) and M1, having direct ( P 1 ) or inverse ( P 2 ) block sequences; copolymers of G2 –G4 and M1, having inverse block sequences and irregular, head-to-head in places, microstructures of the poly(glycolide) blocks ( P 3 –P7 ); and copolymers of G2 and M1, having solely alternating head-to-tail microstructures of the poly(glycolide) blocks and direct (P8 ) or inverse (P9 ) block sequences, have been synthesized. DLS studies have shown that, after deprotection, the copolymers P 1′ –P9′ form liposomal particles in aqueous medium, differing considerably in their colloidal behavior, which depended on the length of the polyamine fragment and the nature of the lipophilic block. The ability of P 1′ –P9′ to deliver the plasmid pEGFP-N1 into cultured HEK293T cells (transfection efficiency) has been assessed at N/P ratios of the corresponding polyplexes in the range 1:1–50:1 by flow cytometry and further confirmed by fluorescence microscopy. Transfection experiments have demonstrated that the CARTs P 1′, P 4′, and P 6′, containing ten (2-oxyethyl)glycine fragments, are about four times more efficient in delivering pDNA than commercial agents (Lipofectamine™ 3000, PEI MAX, X-tremeGENE™ 9, and GenJet™ In Vitro DNA Transfection Reagent). A correlation between the results of those studies and DLS / ζ-potential measurements has been established for P 1′ and P 4′ : the transfection is efficient, if N/P ratios are equal to those favoring ζ-potential inversion at physiological pH. We conclude that glycolide-based CARTs show significant promise for further development as non-viral NA delivery vehicles and that DLS should be regarded as an efficient method of primary screening of amphiphilic copolymers, as well as copolymer-NA complexes and formulations thereof.